Climate Change Vulnerability of Freshwater Fishes of the San Francisco Bay Area - Rebecca M. Quiñones; Peter B. Moyle (San Francisco Estuary and Watershed Science, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--> Rebecca M. Quiñones and Peter B. Moyle doi: http://dx.doi.org/10.15447/sfews.2014v12iss3art3 Climate change is expected to progressively shift the freshwater environments of the San Francisco Bay Area (SFBA) to states that favor alien fishes over native species. Native species likely will have more limited distributions and some may be extirpated. Stream-dependent species may decline as portions of streams dry or become warmer due to lower flows and increased air temperatures. However, factors other than climate change may pose a more immediate threat to native fishes. Comparison of regional vs. statewide vulnerability (baseline and climate change) scores suggests that a higher proportion (56% vs. 50%) of SFBA native species, as compared to the state’s entire fish fauna, are vulnerable to existing anthropogenic threats that result in habitat degradation. In comparison, a smaller proportion of SFBA native species are vulnerable to predicted climate change effects (67% vs. 82%). In the SFBA, adverse effects from climate change likely come second to estuarine alteration, agriculture, and dams. However, the relative effect of climate change on species likely will grow in an increasingly warmer and drier California. Maintaining representative assemblages of native fishes may require providing flow regimes downstream from dams that reflect more natural hydrographs, extensive riparian, stream, and estuarine habitat restoration, and other management actions, such as modification of hatchery operations. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->